Complete mitochondrial genome characteristics and phylogenetic position of Lycodes brevipes Bean, 1890. Issue 1 (2nd January 2019) - Li, Yuan; Feng, Ji; Song, Puqing; Zhang, Nan; Li, Hai; Lin, Longshan
Abstract: Lycodes brevipes is one of the representative species of zoarcid fishes with little genetic information. The complete mitochondrial genome sequence of L. brevipes was sequenced by long PCR and primer walking methods. The mitogenome is a circular molecule of 16, 537 bp in length including the structure of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes and two non-coding regions (origin of light strand replication and control region). The present study also revealed the phylogenetic relationship of this species at the molecular level using NJ algorithm. The mitogenome of L. brevipes provides essential genetic data for further phylogenetic and evolutionary analyses.